HISTO-MORPHOLOGICAL STUDY OF FUNCTIONAL OVERLOAD (CLINICAL EXPERIMENTAL STUDY) - Alketa Qafmolla; Doriana Agop Forna; Ruzhdie Qafmolla; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2024)
Traumatic occlusion function is a continuous overload of dental system in chewing function which causes various damage in periodontal. This overload is visible not only in the full dental system, but also in the lack of teeth. Histo-morphological changes are noticed not only in the soft tissues but also in the periodontal and alveolar process with their atrophy. The aim of our study: is to investigate the Histo-morphological changes in the periodontal of experimental animals (guinea pig) comparing them to the morphological changes of the patients. Material and Methods: In this study we have investigated and treated 88 patients at the age of 20 - 70 for a period of more than 10 years. In our study, we have taken into consideration the causing factors and consequences of functional overload in the oral cavity. We have also studied the histo-morphological changes of functional overload in the experimental animals. Results and discussion: The main cause of functional overload of teeth is the absence of substitution for a long period of time and the prosthesis which are badly put. We noticed macroscopic and microscopic changes in the periodontal of patients and animals too. In the patients, the macroscopic changes were gingival hypertrophy, the damage of contact point, the teeth movability and their displacement. Radiology showed us vertical and horizontal atrophy. In the experimental animals histo-morphological changes were shown in the damage of periodontal ligaments, hematopoietic disorders of pulp and necrotic lesions. The results of clinical treatment of the patients have been valued for a period of time about 5-15 years based on the subjective and radiological data before and after treatment where functional overload interruption was observed. Conclusions: To avoid histo-morphological changes that are caused by functional overload of teeth remained in the oral cavity; the prosthetic treatment of the lack of teeth with various kinds of prosthesis should absolutely be done.